دراسة نقدية وتحليلية لرواية تاريخية "الطلسم" لوالتر سكوتAnalytical and critical study of the historical novel “Talisman” by Walter Scott (Al-Qamar, 2021)
During a truce between the Christian armies taking part in the third Crusade, and the infidel forces under Sultan Salahuddin, Sir Kenneth, on his way to Syria, encountered a Saracen Emir, whom he unhorsed, and they then rode together, discoursing on love and necromancy, towards the cave of the hermit Theodoric of Engaddi. This hermit was in correspondence with the pope, and the knight was charged to communicate secret information. Having provided the travelers with refreshment, the anchorite, as soon as the Saracen slept, conducted his companion to a chapel, where he witnessed a procession, and was recognized by the Lady Edith, to whom he had devoted his heart and sword. He was then startled by the sudden appearance of the dwarfs, and, having reached his couch again, watched the hermit scourging himself until he fell asleep. About the same time Richard Coeur de Lion had succumbed to an attack of fever, and as he lay in his gorgeous tent at Ascalon, Sir Kenneth arrived accompanied by a Moorish physician, who had cured his squire, and who offered to restore the king to health. Philip of France at length persuaded him to refer the matter to the council, and Sir Kenneth was charged to watch the English standard until daybreak, with a favorite hound as his only companion. Soon after midnight, however, the dwarf Necbatanus approached him with Lady Edith's ring, as a token that his attendance was required to decide a wager she had with the queen; and during his absence from his post the banner was carried off, and his dog severely wounded. Overcome with shame and grief, he was accosted by the physician, who dressed the animal's wound, and, having entrusted Sir Kenneth with Salahuddin's desire to marry the Lady Edith, proposed that he should seek the Saracen ruler's protection against the wrath of Richard. The valiant Scot, however, resolved to confront the king and reveal the Sultan's purpose; but it availed him not, and he was sentenced to death, in spite of the intercessions of the queen and his lady-love; when the hermit, and then the physician, arrived, and Richard having yielded to their entreaties, Sir Kenneth was simply forbidden to appear before him again. A procession of the Christian armies and their leaders had already been arranged in token of amity to Richard; and as they marched past him, seated on horseback, with the slave holding the hound among his attendants, the dog suddenly sprang at the Marquis Conrade, who was thus convicted of having injured the animal, and betrayed his guilt by exclaiming, "I never touched the banner." Not being permitted to fight the Teuton himself, the king undertook to provide a champion, and Salahuddin to make all needful preparations for the battle. Accompanied by Queen Berengaria and Lady Edith, Richard was met by the Saracen with a brilliant retinue, and discovered, in the person of his entertainer, the physician who had cured his fever, and saved Sir Kenneth, whom he found prepared to do battle for him on the morrow, with the hermit as his confessor. The encounter took place soon after sunrise, in the presence of the assembled hosts, and Conrade, who was wounded and unhorsed, was tended by the Sultan in the grand-master's tent, while the victorious knight was unarmed by the royal ladies, and made known by Richard as the Prince Royal of Scotland. At noon the Sultan welcomed his guests to a banquet, but, as the grand-master was raising a goblet to his lips, Necbatanus uttered the words accipe hoc, and Salahuddin decapitated the templar with his saber; on which the dwarf explained that, hidden behind a curtain, he had seen him stab his accomplice the Marquis of Montserrat, obviously to prevent him from revealing their infamous plots, while he answered his appeal for mercy in the words he had repeated. The next day the young prince was married to Lady Edith, and presented by the Sultan with his talisman, the Crusade was abandoned, and Richard, on his way homewards, was imprisoned by the Austrians in the Tyrol.
Keywords: Walter Scott; historical; “al-Talism”; analytical and critical study